2022
DOI: 10.2478/ats-2022-0014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mycorrhizal inoculation and organic fertiliser on bioremediation of spent engine oil contaminated soil

Abstract: Hydrocarbon-related environmental pollution is a major environmental hazard due to its toxicity and widespread presence in the environment, resulting in stunted growth of soil microorganisms, plants, and animals. This study was therefore conducted to evaluate the effect of mycorrhizal inoculation and compost made from Cocoa Pod Husk (CPH) and cattle dung in the bioremediation of Spent Engine Oil (SEO)-contaminated soil. About 2.5 kg of sterilised soil was contaminated with SEO at different concentrations: 0, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Mycorrhizal application resulted in enhanced TPH degradation in the SEO contaminated soil. A similar result was also obtained by Nkereuwem et al (2022Nkereuwem et al ( , 2020a where they observed reductions in TPH content of crude oil-contaminated soil. The reduction in TPH content could be due to the fact that mycorrhizal fungi interact with some other beneficial soil organisms in order to achieve complete clean-up of polluted soils (Chibuike, 2013).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Mycorrhizal application resulted in enhanced TPH degradation in the SEO contaminated soil. A similar result was also obtained by Nkereuwem et al (2022Nkereuwem et al ( , 2020a where they observed reductions in TPH content of crude oil-contaminated soil. The reduction in TPH content could be due to the fact that mycorrhizal fungi interact with some other beneficial soil organisms in order to achieve complete clean-up of polluted soils (Chibuike, 2013).…”
Section: Discussionsupporting
confidence: 83%
“…Cattle rumen digesta is recommended for use in bioremediation because it enhances soil nutrient utilization and reduces pollution (Cherdthong, 2020). It is possible to both remediate the contaminated soil in situ and revegetate the region at the same time if the right mycorrhizal fungus is introduced into the soil (Tangahu et al, 2011;Nkereuwem et al, 2022). Over time, bioremediation technology has demonstrated positive results in eliminating hydrocarbon levels from affected ecosystems (Nkereuwem et al, 2022;Nkereuwem et al, 2020a;Adeleye et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation